Public Policy Management through the Program Keluarga Harapan (PKH) in Realizing Equal Primary and Secondary Education in Bandung Regency - Munawaroh, Siti Nurhasanah; Rahmat, Nanang; Hidayat, Asep Taufik; Nashrulloh, Yusuf; Napsin, Napsin; Hartoto, Hartoto (International Journal of Economics (IJEC), 2024)
Education is something that is very essential in the process of humanizing a cultured society. In other words, everyone in this world has the right to educate according to his abilities. However, in reality, note all children have received education. The purpose of this study was to determine the Program Keluarga Harapan (PKH) in realizing equal distribution of primary and secondary education for the community. This study used a qualitative descriptive method with data collection techniques used were observation, interviews, and documentation studies. Based on the research results, it is obtained that the description of the Program Keluarga Harapan (PKH) in realizing equal distribution of primary and secondary education can be conveyed: 1) The PKH program is a planned, measured, directed activity by planning, organizing, implementing, evaluating and following up in an effort to realize equitable primary and secondary education; 2) The PKH program has been running in accordance with the implementation procedure, fulfilling the rights and obligations of program recipients as well as the follow-up of program implementation. 3) the obstacle is the lack of understanding of PKH program recipients and local officials about the PKH program implementation procedures and the low motivation of PKH recipients to continue their education to a higher level. 4). The step in coming is to coordinate with the village government, sub-district coordinators and supervision in providing understanding and education about the PKH program and providing motivation to PKH recipients about the importance of education.